DEVELOPMENT GUIDELINES FOR AN AIRSIDE VEHICLE DRIVERS’ CURRICULUM AT SUVARNABHUMI AIRPORT - Samransuk, Sawat; Temkaew, Waraporn; Khamproh, Thanyarat (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The independent study of Development Guidelines for an Airside Vehicle Driver’s Curriculum at Suvarnabhumi Airport has the following objectives: (1) to evaluate the standard of drivers who took airside driving refreshment training at Suvarnabhumi airport and (2) to provide guidance on developing an airside driving training course at Suvarnabhumi airport. The sampling group was selected from 177 airside drivers who took the refreshment training course at Suvarnabhumi airport. These data were analyzed using basic statistics such as frequency, percentage, content analysis, and descriptive presentation, and the research studies were conducted using a mixed method by the following sources; two experts from the Airside Driving Training Course. The study shows that evaluating the standards of airside drivers who took the refreshment training course reveals that their assessment through the rules and regulations for the airside driving test complied with the Civil Aviation Authority of Thailand, Regulations of Civil Aviation Authority of Thailand No.14 on Aerodromes. Such tests are composed of 20 questions and contain the following 12 topics in accordance with ICAO Annex 14 Aerodromes and the guidance on developing an airside driving training course reveals that there should be practical training through a simulator program in normal and emergency situations to develop drivers’ solving skills. For the training period, one day is recommended.